PERBEDAAN PENGARUH LATIHAN SENAM AEROBIK HIGH IMPACT DAN LOW IMPACT TERHADAP PENURUNAN PERSENTASE LEMAK TUBUH DITINJAU DARI STATUS GIZI (Studi Eksperimen pada Anggota Sanggar Senam Vira Watukelir Weru Sukoharjo) - HARTINI HARTINI (Universitas Tunas Pembangunan, 2015)
THE DIFFERENCE EFFECT OF TRAINING AEROBIC GYMNASTICS HIGH IMPACT AND LOW IMPACT ON DECREASE IN BODY FAT PERCENTAGE JUDGING FROM NUTRITION STATUS (Experimental Study on The Members of a Shrine Gymnastic Vira Watukelir Weru Sukoharjo). This research aims to find out: (1) the difference effect between of training aerobic gymnastics high impact and low impact on decrease in body fat percentage, (2) the difference of decrease in body fat percentage between the members of the shrine gymnastic with acceptable and obese nutrition status, (3) the interaction effect between training gymnastics with nutrition status on decrease in body fat percentage. This research employed an experimental method with 2 x 2 factorial design. The population of the research in the members of a shrine gymnastic Vira Watukelir Weru Sukoharjo. The sampling technique was purposive random sampling, the size of the samples taken are as much as 40 members of a shrine gymnastic. ANOVA was used to analyzing data, the data analysis prerequisite test was done using the sample normality test (Lilliefors test with Î± = 0.05%) and variance homogeneity test (Bartlett test with Î± = 0.05%). Based on the result of the analysis, conclusions are drawn as follows: (1) There was difference between the effect of training aerobic gymnastics high impact and low impact on decrease in body fat percentage. The effect of training aerobic gymnastics high impact is higher than the training aerobic gymnastics low impact, (2) there was difference of decrease in body fat percentage between the members of the shrine gymnastic with acceptable and obese nutrition status. The effect of decrease in body fat percentage between the members of the shrine gymnastic with acceptable nutrition status this higher than the one with obese nutrition status, (3) there was interaction effect between training gymnastics with nutrition status on decrease in body fat percentage. The members of the shrine gymnastic with acceptable nutrition status has according if it is training aerobic gymnastics high impact. The members of the shrine gymnastic with obese nutrition status has according if it is training aerobic gymnastics low impact.